Effect of the ACAA1 Gene on Preadipocyte Differentiation in Sheep - Wang, Yanli; Li, Xin; Cao, Yang; Xiao, Cheng; Liu, Yu; Jin, Haiguo; Cao, Yang (Frontiers in Genetics, 2021)
Acetyl-CoA acyltransferase 1 (ACAA1) functions as a key regulator of fatty acid β-oxidation in peroxisomes by catalyzing the cleavage of 3-ketoacyl-CoA to acetyl-CoA and acyl-CoA, which participate in the extension and degradation of fatty acids. Thus, ACAA1 is an important regulator of lipid metabolism and plays an essential role in fatty acid oxidation and lipid metabolism. Our previous study findings revealed that ACAA1 is closely associated with the peroxisome proliferator-activated receptor (PPAR) signaling and fatty acid metabolism pathways, which are involved in fat deposition in sheep, leading to our hypothesis that ACAA1 may be involved in fat deposition by regulating lipid metabolism. However, the associated molecular mechanism remains unclear. In the present study, to assess the potential function of ACAA1 in sheep preadipocyte differentiation, we knocked down and overexpressed ACAA1 in sheep preadipocytes and evaluated the pattern of ACAA1 gene expression during preadipocyte differentiation by qRT-PCR. ACAA1 was significantly expressed in the early stage of adipocyte differentiation, and then its expression decreased. ACAA1 deficiency increased lipid accumulation and the triglyceride content and promoted sheep preadipocyte differentiation, whereas ACAA1 overexpression inhibited adipogenesis and decreased lipid accumulation and the triglyceride content. Simultaneously, we demonstrated that ACAA1 deficiency upregulated the expression of the adipogenic marker genes PPARγ and C/EBPα in sheep preadipocytes but ACAA1 overexpression inhibited the expression of these markers, indicating that ACAA1 affects lipid metabolism by regulating adipogenic marker genes. Our results may promote a better understanding of the regulation of adipogenesis by ACAA1.